INTEGRATING ISLAMIC DESIGN PRINCIPLES FOR ACHIEVING FAMILY PRIVACY IN RESIDENTIAL ARCHITECTURE - Babangida, Hamza; Katsina, Halima Sani (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2018)
Islamic Design Principles (IDP) are general guides in the context of the Islamic legal system (Sharia) abstracted for application in the management of the existing Muslim built environment and which could be used for the designing new buildings. Accordingly, they were developed from various Sharia sources among which include the Qur'an and the Hadith, as primary sources. The aim of this paper is to identify Islamic Design Principles which apply to architecture and to use same to demonstrate how they could be applied to achieve family privacy in residential design of the Muslim faithful. The research methodology involved literature search on extant works which identified Islamic Principles and their relevance to residential architecture on one hand and documentation of floor plans of existing houses designed for and occupied by Muslims in Nigeria. A four bedroom duplex among the documented houses was used to demonstrate how family privacy could be achieved using the Islamic Design Principles (IDP) at various design stages such as spatial rearrangement, reorientation, and reconfiguration of functional spaces without compromising global design criteria. In the redesigned floor plans, the design elements that were integrated include those which affected bedrooms, living rooms and other spaces for family interactions to reflect family privacy needs. Overall, the outcome of this paper adds to our understanding of the role the Islamic Design Principles (IDP) could play in no distant future on novel design approaches that support the use of new structural forms, shape and design elements which provides to privacy needs of Muslim faithful as well as satisfy universal design requirements. This paper will find practical implication if it is used as theoretical as well practical support to professionals in designing residences which address specific spiritual values of residentsÂ Â